Correlação entre a escala internacional de acidente vascular cerebral do Instituto Nacional de Saúde (NIHSS) e a penetração laríngea e aspiração laringotraqueal no acidente vascular cerebral isquêmico - Ribeiro, Priscila Watson [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The use of the National Institutes of Health Stroke Scale (NIHSS) have been proposed as a screening tool, as clinical predictors of the presence of oropharyngeal dysphagia and an indicator of the safe way of feeding in individuals after stroke, even these not scoring the swallowing disorder. However, most studies recommend the use of clinical parameters in evaluating of swallowing, which hinder identification of specific alterations that could help to decide the way of feeding and the safe consistency. Therefore, this study aimed to determine the correlation between the NIHSS score and the presence of laryngeal penetration and tracheal aspiration in individuals after ischemic stroke, using videofluoroscopic evaluation of swallowing. Seventy-four after ischemic stroke individuals were evaluated; they had been submitted to neurological and NIHSS evaluation. They were divided into four groups according to the severity of stroke in NIHSS score, G1 (0-4 points), G2 (5-10 points), G3 (11-20 points) and G4 (≥ 20 points). Two of these individuals were excluded from the swallowing clinical assessment because they have severe neurological impairment measured by NIHSS. Seventy two subjects were submitted to swallowing clinical evaluation and videofluoroscopy of swallowing, performed on the same day, using thin pasty e liquid consistencies , observing the presence of laryngeal penetration and tracheal aspiration. The absence of a statistically significant correlation between the NIHSS score and the presence of laryngeal penetration with thin pasty (P = 0.3270) and liquid (P= 0.8138) was verified. Likewise, there was no correction between the NIHSS and the presence of tracheal aspiration with thin pastoso (P = 0.3714) and liquid (P=0.6292). The laryngeal penetration occurred in only 06 (8.33%) individuals with thin pasty, distributed in G1 (66.6%) and G2 (33.3%) of the NIHSS. With liquid, laryngeal penetration ...

Estudos têm proposto a utilização da Escala Internacional de Acidente Vascular Cerebral do Instituto Nacional de Saúde (NIHSS) como um instrumento de triagem, como preditor clínico da presença de disfagia orofaríngea e indicador de via de alimentação nos indivíduos pós-AVC, mesmo este não pontuando o distúrbio de deglutição. No entanto, a maioria deles preconizou o uso de parâmetros clínicos na avaliação da deglutição, o que dificulta a identificação de alterações específicas que podem direcionar a conduta sobre a via e consistência de alimentação. Sendo assim, este estudo teve como objetivo verificar a correlação entre a pontuação obtida no NIHSS e a presença de penetração laríngea e aspiração laringotraqueal nos indivíduos pós-AVC isquêmico, utilizando o exame de videofluoroscopia da deglutição. Participaram deste estudo 74 indivíduos pós-AVC isquêmico submetidos à avaliação neurológica e aplicação do NIHSS. Os indivíduos foram divididos em quatro grupos conforme a gravidade do AVC na pontuação do NIHSS, sendo G1 (0-4 pontos), G2 (5-10), G3 (11-20) e G4 (≥ 20). Destes indivíduos, dois foram excluídos da avaliação fonoaudiológica da deglutição por apresentarem comprometimento neurológico grave mensurado pelo NIHSS. 72 indivíduos foram submetidos à avaliação fonoaudiológica clinica e ao exame videofluoroscópico da deglutição, realizados no mesmo dia, com o pastoso fino e líquido ralo, observando a presença de penetração laríngea e aspiração laringotraqueal. Foi verificada a ausência de correlação estatisticamente significante entre a pontuação no NIHSS e a presença de penetração laríngea com pastoso fino ...
Keywords: Acidente vascular cerebral; Isquemia cerebral; Disturbios da deglutição; Cerebrovascular disease